Police narrative in Perú: the case of Escalas by César Vallejo - Cachay Luna, Christian Bryan (2023)
The consolidation of the literary field in our country arose with the literary histories at the beginning of the 20th century. These studies are precisely the ones that will define or refute the canon up to our time. In this sense, the police narrative always occupied a marginal, but not invisible, place, which is why it is necessary to periodize its formation and reception. This paper places Vallejo in the center of the debate, because, first, it studies the context of Peruvian narrative at the beginning of the twentieth century and, specifically, the position of the police genre; second, the research will expose the characteristics that some of the stories of Escalas have to be classified as police narrative.